2022
DOI: 10.3390/nu14245299
|View full text |Cite
|
Sign up to set email alerts
|

Isocaloric Diets with Different Protein-Carbohydrate Ratios: The Effect on Sleep, Melatonin Secretion and Subsequent Nutritional Response in Healthy Young Men

Abstract: This study aimed to determine the short-term effect of two isocaloric diets differing in the ratio of protein–carbohydrate on melatonin levels, sleep, and subsequent dietary intake and physical activity in healthy young men. Twenty-four healthy men took part in a crossover design including two sessions of three days on isocaloric diets whether high-protein, low-carbohydrate (HPLC) or low-protein, high-carbohydrate (LPHC) followed by 24-h free living assessments. Sleep was measured by ambulatory polysomnography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Previous studies found resistant dextrin and resistant starch decreased the intestinal levels of secondary bile acids including DCA in humans and rats. 7,37,55,64 It is noteworthy that DCA is a cytotoxic bile acid, along with bacterial lipopolysaccharide products transported to the liver from the intestine through the portal vein and causing hepatic steatosis. 65 High dietary fiber intake has been reported to decrease the levels of secondary bile acids, for instance, a previous study found that the use of 3% dietary fiber decreased the GDCA level in the bile of piglets and was associated with the serum TC concentrations.…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found resistant dextrin and resistant starch decreased the intestinal levels of secondary bile acids including DCA in humans and rats. 7,37,55,64 It is noteworthy that DCA is a cytotoxic bile acid, along with bacterial lipopolysaccharide products transported to the liver from the intestine through the portal vein and causing hepatic steatosis. 65 High dietary fiber intake has been reported to decrease the levels of secondary bile acids, for instance, a previous study found that the use of 3% dietary fiber decreased the GDCA level in the bile of piglets and was associated with the serum TC concentrations.…”
Section: Papermentioning
confidence: 99%
“…5,6 A study on healthy young men found that a low protein-carbohydrate ratio diet improved sleep quality and increased melatonin secretion compared with an isocaloric diet with a high protein-carbohydrate ratio after the three-day intervention. 7 More and more studies have found that the long-term intake of a high amount of protein can induce the dysbiosis of the gut microbiota, contribute to chronic inflammation and be detrimental to metabolic homeostasis and energy balance. 3,4,8 Moreover, our previous study showed that 38% and 50% crude protein diets upregulated ACC-1 expression and downregulated AMPK-α2 expression, which might lead to accelerated hepatic cholesterol accumulation in rats after 6 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Ramón-Arbués, E et al [ 2 ] revealed that among 868 Spanish students, unhealthy eaters were more likely to also be bad sleepers; an imbalanced intake of vegetables, fruits, dairy products, lean meats, legumes, sweets, and sugary soft drinks was associated with lower sleep quality. Saidi, O et al [ 3 ] depicted in a crossover study of 24 healthy men, that increased carbohydrate intake was associated with better sleep quality and increased melatonin secretion. The protocol design included two sessions of three days on isocaloric diets; high-protein, low-carbohydrate (HPLC), or low-protein, high-carbohydrate (LPHC) followed by 24 h free living assessments.…”
mentioning
confidence: 99%